Preservation Rhinoplasty: A New Approach to Mestizo Noses - Norman Anco, MD; Gonzalo Caballero, MD; Gerardo Adrianzen, MD (Plastic and Reconstructive Surgery, Global Open, 2023)
Background:. Preservation rhinoplasty is a widely used technique; however, its use on mestizo noses is poorly documented. Our objective was to assess the level of satisfaction of our mestizo patients 1 year after their preservation rhinoplasty. Methods:. The Rhinoplasty Outcome Evaluation (ROE), a Likert-type questionnaire validated in Spanish, was used to assess the level of satisfaction of 14 mestizo patients who underwent preservation rhinoplasty from March to July 2021 at 1 year after their surgery at the Higuereta Clinic in Lima, Peru. Results:. The study included 14 patients, three men and 11 women, who underwent preservation rhinoplasty. A presurgical ROE questionnaire was applied, presenting a minimum value of 6, a maximum value of 21, and a mean of 12. When applied 1 year after surgery, the same ROE questionnaire presented a minimum value of 28, a maximum value of 30, and a mean of 30. The variation had a minimum value of 9 and a maximum value of 23, with a mean of 17 (P < 0.001). Conclusions:. Preservation rhinoplasty can be successfully implemented in mestizo noses with good aesthetic results.